Optimization of Temperature and Drying Time on Flavonoids Levels of Anjasmoro Variety Soybean (Glycine Max) Extract Using Response Surface Methodology - Wardatun, Sri; Indah Puspita Dewi, Anggy; Amalina, Dhaifa Ghaisani Rizkia (FITOFARMAKA: JURNAL ILMIAH FARMASI, 2023)
Soybeans (Glycine max) contain a number of nutritional and health-supporting compounds, such as protein, fibers, phytosterols, and isoflavones. The pharmacological activities of soybeans include improving the immune system, acting as an antioxidant, inhibiting carcinogenesis, and reducing cholesterol levels. Anjasmoro variety is one of the superior varieties of large-seeded soybeans and is in great demand by farmers. The temperature and drying time of soybeans can have an effect on the level of compounds extracted. The aim of this research was to optimize flavonoid extraction from soybeans based on temperature and drying time using the response surface methodology (RSM). The results show that the optimal temperature and drying time of soybeans was obtained at 60.027 °C and 6.036 hours, with optimal flavonoid levels of 21.9707 mg QE/g. The verification results based on laboratory test confirmed that the level of flavonoids at optimal condition was 20.6461 mg QE/g, with a deviation of 6.03 % from prediction value and accuracy results of 93.97 %. The optimal drying temperature and drying time of soybeans can be used to obtain the highest flavonoid levels.